Faktor-Faktor Yang Mempengaruhi Perilaku SADARI Pada Mahasiswa Non Kesehatan Di Universitas Riau - Khairunnisa, Saskia; Huda, Nurul; Dilaruri, Ade (JUKEJ : Jurnal Kesehatan Jompa, 2025)
Breast self-examination (sadari) is a breast cancer examination that aims to detect abnormalities in the breast and as an initial step to prevent breast cancer. This study aims to determine the factors that influence self-examination behavior in non-health students at the University of Riau. This study uses a descriptive correlation design with a cross-sectional approach. The sample of this study was 389 respondents taken using stratified random sampling technique. The results of the chi-square test analysis obtained results from 389 respondents as many as 253 (65%) did not do self-examination, 227 respondents (58.4%) had sufficient knowledge category, 209 (53.7%) showed that respondents had never been exposed to information, 197 (50.6%) category of good family support and 199 (51.2%) peer support was lacking. The results of the statistical test of knowledge with self-examination behavior p = 0.001 <0.05, exposure to information, family and peer support with self-examination behavior p = 0.000 <0.05. Knowledge, exposure to information, family support and peer support have a significant relationship to conscious behavior, while attitude has no relationship to conscious behavior. The suggestion for further researchers is to use direct observation techniques in assessing conscious behavior.